A participatory appraisal of the farming business environment, gender issues and service delivery by veterinary para-professionals in Uganda - Baluka, S. A.; Mugisha, A.; Ofungi, J.; Tukahirwa, L.; Mugabi, K. (International Journal of Veterinary Sciences and Animal Husbandry, 2023)
This study assessed the farming business environment and gender issues and their effect on service delivery by the veterinary para-professionals (VPPs) in Sembabule and Soroti districts. The study employed Participatory Rural Appraisal research method. The study found that treatment of animals (39%), vaccination (20%), and farmer advisory service (19.5%) were the services most demanded by smallholder livestock farmers. On the other hand, the production system of the study area was of low input low output system. Tethering and communal grazing were the most practiced livestock production systems in the study areas. Majority of farmers preferred Male VPPs to female VPPs. The reason given was that women extension agents are very few in the field and they slow in responding to case calls. This could be affecting opportunities for women small holder farmers to access veterinary services since it has been proven in most cases, women farmers prefer female extension agents.